HUBUNGAN ANTARA PENGETAHUAN TENTANG HIV/AIDS DAN SIKAP TERHADAP VCT PADA MAHASISWA DIII KEBIDANAN - Fitri Pebrianti; Ika Sumiyarsi Sukamto; Mujahidatul Musfiroh (Jurnal Ilmiah Maternal, 2017)
ABSTRACT Midwifery students are including groups that have risk to be affected by HIV/AIDS are expected to know about preventive action, one of them is HIV/AIDS early detection through VCT (Voluntary Counseling Testing). The purpose of this research is to find out the correlation between knowledge of HIV/AIDS and attitudes toward VCT at DIII midwife program’s stu- dents. Research method used analytical observational method with cross sectional approach. The sampling technique used probability samples with random sampling type. The samples were 118 respondents who fulfill the retraction criteria. Measurement tool was questionnaire, and the statistical analysis was Kendall’s Tau. Research reasul show the HIV/AIDS knowledge who had good level was about 82 respondents (69.5%). Positive attitude toward VCT was 79 respondents (66.9%). Result of hypothesis analysis used Kendall’s tau_b obtained significance value (p value) 0.000 (p 0,05) and correlation value (r) 0,473. There is a worthwhile corre- lation between knowledge of HIV/AIDS and attitudes toward VCT at DIII midwife program’s students. The correlation direction was positive with sufficient strength. Better the knowledge of HIV/AIDS, the more positive the attitude towards VCT. Keywords : Knowledge of HIV/AIDS, VCT Attitudes, Students ABSTRAK Mahasiswa kebidanan termasuk kelompok beresiko tertularnya HIV/AIDS diharapkan da- pat mengetahui tindakan pencegahan, salah satunya dengan deteksi dini HIV/AIDS melalui VCT (Voluntary Counseling Testing). Penelitian bertujuan untuk mengetahui hubungan antara pengetahuan tentang HIV/AIDS dan sikap terhadap VCT pada mahasiswa DIII Kebidanan. Metode penelitian menggunakan metode observasional analitik dengan pendekatan cross sec- tional. Teknik pengambilan sampel menggunakan sampel probabilitas dengan jenis pengambi- lan sampel secara acak. Besar sampelnya yaitu 118 responden yang memenuhi kriteria retriksi. Alat ukur berupa kuisioner. Uji statistik yaitu Kendall’s Tau. Hasil penelitian menunujukkan tingkat pengetahuan tentang HIV/AIDS pada responden adalah baik sebanyak 82 responden (69.5%). Sikap positif terhadap VCT sebanyak 79 responden (66.9%). Hasil uji hipotesis den- gan kendall’s tau_b diperoleh nilai significancy (p value) sebesar 0,000 (p0,05) dan nilai korelasi (r) 0,473. Terdapat hubungan yang bermakna antara Pengetahuan tentang HIV/AIDS dan Sikap terhadap VCT pada Mahasiswa DIII Kebidanan. Arah korelasi positif dengan kekua- tan cukup. Semakin baik pengetahuan tentang HIV/AIDS maka semakin positif sikap terhadap VCT. Kata Kunci : Pengetahuan HIV/AIDS, Sikap VCT, Mahasiswa